2021
DOI: 10.1016/j.adaj.2021.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Dental trainees’ mental health and intention to leave their programs during the COVID-19 pandemic

Abstract: Background. Dental trainees (dental students, graduate students, and postdoctoral residents) are at increased risk of experiencing poor mental health, which can lead to intentions to leave their program, especially during the COVID-19 pandemic.Methods. The authors invited 355 dental trainees at the University of Washington School of Dentistry to complete an 83-item questionnaire in August and September 2020. The outcome analyzed was intention to leave their programs. There were 4 self-reported predictors: anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 31 publications
0
35
1
1
Order By: Relevance
“…In this study, it was also found that the sources of stress, most associated with Portuguese medical students’ burnout during the pandemic, were, apart from those related to the high course demands and unhealthy lifestyle, the COVID-19 related restrictions imposed on training and socializing [ 30 ]. Other studies confirm the COVID-19 impact on medical [ 35 , 36 ] and dentistry [ 37 , 38 ] students’ burnout.…”
Section: Introductionmentioning
confidence: 65%
“…In this study, it was also found that the sources of stress, most associated with Portuguese medical students’ burnout during the pandemic, were, apart from those related to the high course demands and unhealthy lifestyle, the COVID-19 related restrictions imposed on training and socializing [ 30 ]. Other studies confirm the COVID-19 impact on medical [ 35 , 36 ] and dentistry [ 37 , 38 ] students’ burnout.…”
Section: Introductionmentioning
confidence: 65%
“…A total of 96 duplicate articles were deleted and 166 were excluded after a first screening of the titles and abstracts. After reading the remaining 43 articles in full, we finally included 13 in our meta-analysis [47][48][49][50][51][52][53][54][55][56][57][58][59]. Exclusion reasons are detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors also had studied the impact of the COVID-19 pandemic among dental students. Chi et al (19) found that 69% of survey dental students in Washington (USA) reported a negative impact in their mental health, with manifestations such as anxiety, depression or burnout, which could lead students to drop out of school.…”
Section: Related Findingsmentioning
confidence: 99%